Sanskritization and Caste Opposition: A Shift from Ritual to Politico-economic Power - B.K., Amar Bahadur (Himalayan Journal of Sociology and Anthropology, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <mce:style><! st1\:*behavior:url(#ieooui) –> <!–[endif] –> <!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400; –> <!–[endif] –> Although ‘Sanskritization' had been a popular term among sociologists and anthropologists during the decades of fifties and sixties, the concept gradually faltered after modernization and westernization took precedence over it. However, the concept has again been able to get attention of intellectuals, especially of those who involve in discourses on Dalit in Nepal, engaged in imitating the higher castes especially after the reinstatement of democracy in 1990 that opened up the new avenues for caste mobility and opposition. Teetotalism, vegetarianism, temple building and its worship, fasting, reading religious books, discarding carcass, wearing sacred thread etc by Dalits are some of the examples of imitations. It is commonly presumed by the Nepalese social scientists especially by Dalits that such imitations are Sanskritization. Therefore, given the changing caste structure and function in the Nepalese society the present article attempts to answer questions as to; whether such imitations are Sanskritization, what the relationship is between imitation and caste notion and hierarchy and how caste has been functioning in present society and is understood by Dalit. The paper has been prepared on the basis of a field work in four Dalit settlements in Pokhara for four months. DOI: http://dx.doi.org/10.3126/hjsa.v3i0.1492 Himalayan Journal of Sociology and Anthropology Vol.III, Sept. 2008 p.1-10